'True Crime and…': The Hybridisation of True Crime Narratives on YouTube. (March 2022) - Hobbs, Simon; Hoffman, Megan
Abstract : Digital platforms have heralded a renaissance in true crime production and engagement, providing previously marginalised voices with opportunities to challenge longstanding – and often problematic – genre conventions. Whilst significant consideration has been given to professional streaming platforms and aural user-generated mediums such as podcasts, few studies have explored visual user-generated content such as that appearing on YouTube. In order to explore these new but increasingly popular forms, we focus on the videos of Stephanie Soo, Samantha Taylor and Bailey Sarian, who combine true crime narratives with the popular YouTube staples of Mukbang, ASMR and makeup tutorial videos. Our work examines the repercussions of true crime becoming a unique selling point within these YouTube subgenres and considers the ethical consequences of using the true crime genre's paradigms to bring greater attention, likes and subscribers to established YouTube channels. We observe that these videos are contradictory documents which provide a potentially empowering outlet for female-led true crime while simultaneously replicating the troubling trends that have marked the genre as a space in which the bodies of victims are often exploited as entertainment.